2014
DOI: 10.1039/c4cc06304j
|View full text |Cite
|
Sign up to set email alerts
|

Formation of persulphate from sodium sulphite and molecular oxygen catalysed by H5PV2Mo10O40– aerobic epoxidation and hydrolysis

Abstract: The H5PV2Mo10O40 polyoxometalate catalysed the electron transfer oxidation of sulphite to yield a sulphite radical, SO3˙(-) that upon addition of O2 yielded a peroxosulphate species efficient for the H5PV2Mo10O40 catalysed epoxidation of alkenes. The acidic polyoxometalate further catalysed hydrolysis of the epoxide to give vicinal diols in high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…388 Notably, Rubinstein et al reported a protocol using molecular oxygen under atmospheric pressure as the oxidant. 389 In the presence of the inorganic polyoxometalate catalyst (H 5 PV 2 Mo 10 O 40 ), sodium sulfite is oxidized to mono-oxygen persulfate, which in turn acts as the epoxidation agent.…”
Section: Acs Catalysismentioning
confidence: 99%
“…388 Notably, Rubinstein et al reported a protocol using molecular oxygen under atmospheric pressure as the oxidant. 389 In the presence of the inorganic polyoxometalate catalyst (H 5 PV 2 Mo 10 O 40 ), sodium sulfite is oxidized to mono-oxygen persulfate, which in turn acts as the epoxidation agent.…”
Section: Acs Catalysismentioning
confidence: 99%
“…There is also a report that H 5 PV 2 Mo 10 O 40 supported on carbon nitride can oxidize benzene with an additional reducing agent, but this reaction should be checked to see if the support acts as an electron donor. Finally, sodium sulfite has also been reported as a convenient reducing agent toward the epoxidation and then acid catalyzed hydrolysis of alkenes to diols catalyzed by H 5 PV 2 Mo 10 O 40 as a bifunctional catalyst …”
Section: Activation Of Dioxygenmentioning
confidence: 99%
“…trans-epoxides are obtained. In 2014, a protocol for the in situ formation of monooxygen persulfate from inexpensive Na 2 SO 3 /O 2 was described, 92 using an inorganic polyoxometalate catalyst (H 5 PV 2 Mo 10 O 40 ), avoiding the use of sacrificial aldehydes in the epoxidation process. The epoxidation of methyl oleate or high oleic fatty acid methyl esters from different vegetable oils in a one-pot reaction over supported copper catalysts has also been reported using molecular O 2 and cumene as the oxygen carrier.…”
Section: Short Review Syn Thesismentioning
confidence: 99%